Modern Agronomy in the 21st Century: Advances, Sustainability and Global Applications - , Ram Gopal; , S. S. Yadav; , Kalyani Pradhan; , Dileep Kumar Tiwari; , Vinod Kumar; , Sandeep Rout; , Narinder Panotra; , Sagar Kashinath Khokale; , Anchal Singh; , Virendra Singh (Archives of Current Research International, 2025)
The systematic review examines the key practices that are transforming agronomy, including precision agriculture, biotechnology, conservation agriculture, and integrated pest management. The article will also discuss the role of digital technologies in enabling data-driven and efficient agronomy practices. The field of agronomy has seen significant advancements in the 21st century, with a focus on increasing crop yields, improving sustainability, and addressing global food security challenges. This article aims to provide an in-depth analysis of the advancements and sustainability of modern agronomy practices in the 21st century, with a focus on their application in India. This article explores the latest developments in agronomy practices, including precision agriculture, biotechnology, conservation agriculture, and integrated pest management. The role of digital technologies in enabling data-driven and efficient agronomy practices. It examines how these practices are being implemented in India and other parts of the world to enhance agricultural productivity while minimising environmental impacts. Role of digital technologies, such as remote sensing, data analytics, and robotics, in enabling more efficient and data-driven agronomy. Furthermore, it highlights the importance of sustainable agronomy practices in the face of climate change, soil degradation, and water scarcity. However, the adoption of agroecology in India faces several challenges, such as the dominance of industrial agriculture, the lack of policy support and incentives, and the need for capacity building and social mobilization mobilization. The article concludes by emphasising the need for continued research, innovation, and knowledge sharing to ensure the long-term sustainability and resilience of global agriculture systems. Modern agronomy has the potential to meet the growing demand for food while safeguarding the planet's natural resources for future generations.